4-Isopropyl-2, 6-bis(1-phenylethyl)aniline 1, an Analogue of KTH-13 Isolated from Cordyceps bassiana, Inhibits the NF-κB-Mediated Inflammatory Response. (27th December 2015) - Yang, Woo Seok; Ratan, Zubair Ahmed; Kim, Gihyeon; Lee, Yunmi; Kim, Mi-Yeon; Kim, Jong-Hoon; Cho, Jae Youl
Abstract : The Cordyceps species has been a good source of compounds with anticancer and anti-inflammatory activities. Recently, we reported a novel compound (4-isopropyl-2, 6-bis(1-phenylethyl)phenol, KTH-13) with anticancer activity isolated from Cordyceps bassiana and created several derivatives to increase its pharmacological activity. In this study, we tested one of the KTH-013 derivatives, 4-isopropyl-2, 6-bis(1-phenylethyl)aniline 1 (KTH-13-AD1), with regard to anti-inflammatory activity under macrophage-mediated inflammatory conditions. KTH-13-AD1 clearly suppressed the production of nitric oxide (NO) and reactive oxygen species (ROS) in lipopolysaccharide (LPS) and sodium nitroprusside- (SNP-) treated macrophage-like cells (RAW264.7 cells). Similarly, this compound also reduced mRNA expression of inducible NO synthase (iNOS) and tumor necrosis factor- α (TNF- α ), as analyzed by RT-PCR and real-time PCR. Interestingly, KTH-13-AD1 strongly diminished NF- κ B-mediated luciferase activities and nuclear translocation of NF- κ B family proteins. In accordance, KTH-13-AD1 suppressed the upstream signaling pathway of NF- κ B activation, including I κ B α, IKK α / β, AKT, p85/PI3K, and Src in a time- and dose-dependent manner. The autophosphorylation of Src and NF- κ B observed during the overexpression of Src was also suppressed by KTH-13-AD1. These results strongly suggest that KTH-13-AD1 has strong anti-inflammatory features mediated by suppression of the Src/NF- κ B regulatory loop.